Stranded! : How Rising Inequality Suppressed US Migration and Hurt Those Left Behind - Bayoumi, Tamim; Barkema, Jelle (Washington, D.C. : International Monetary Fund, 2019)
Using bilateral data on migration across US metro areas, we find strong evidence that increasing house price and income inequality has reduced long distance migration, the type most linked to jobs. For those migrating uphill, from a less to a more prosperous location, lower mobility is driven by increasing house price inequlity, as the disincentives from higher house prices dominate the incentives from higher earnings. By contrast, increasing income inequality drives the fall in downhill migration as the disincentives from lower earnings dominate the incentives from lower house prices. The model underlines the plight of those trapped in decaying metro areas-those 'left behind'.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet